Sustainable Urban Development – Conceptual Approach - Bhargava, Akshey; Manchala, Manjusha; Singhal, Richa; Patel, Unnati; Golhar, Prachi (Journal of Energy Conservation, 2020)
Urbanism and urbanization is a complex term in as much as that it is highly diversified in terms of culture, traditions, religion, social behavior and life, size and capacity, supporting infrastructure, governance, administration, planning approach, trade, so on and so forth. The present scenario is highly sophisticated and alarming in the context of growing and continuous expansion of the urbanization world over leading to associated problems and pose threats to social, environmental, and economic. An effort has been made by the authors of the present paper to conceptualize the parameters for environmental sustainability in urban development.
Keywords: Environment; sustainable sites; urban planning; integrated planning; smart design; policy parameters; concepts